Social perception of natural risks by local residents in developing countries—The example of the coastal area of Benin - TEKA, SEMADEGBE OSCAR; Vogt, Joachim (My University, 2010)
Risk management and planning activities cannot be sustainably and efficiently implemented unless being based on a participative approach resulting from the problem consciousness and perception of the local inhabitants. This requires that the measures linked to problem perception and assessment by local stakeholders, above all by the population affected, are known. This investigation conducted in the flat Beninese coastal lagoon areas aims to assess the local inhabitants’ risk perception. The results are the following: (i) the stakeholders have group-specific ways of risk perception (according to ethnicity, social group, age); (ii) every risk management strategy should be based on the group-specific ways of risk perception and assessment; (iii) the acceptance of a given risk management strategy including interactive ways of participation can be advanced through education, dissemination of risk information as well as through communication between stakeholders.
Keywords: Risk perception; Coastal area; Climate change; Participation; Benin